Utilizing untapped potential of rice fallow of East and North-east India through pulse production - Singh, N. P.; Praharaj, C. S.; Sandhu, J. S. (The Indian Journal of Genetics and Plant Breeding, 2017)
Rainfed areas of the country- characterized by its complex nature, diverse and fragile ecosystem and distress prone production system - play a key role in country’s food production and economy. It is estimated that about 11.695 m ha in India remains fallow after rice harvest, of which around 82% lies in the Eastern India and the rest falls in three southern states viz., Tamil Nadu, Karnataka and Andhra Pradesh. These areas have a vast potential to cultivate low input and low water requiring upland pulse crops (such as lentil, chickpea, lathyrus, mungbean and urdbean). However, depletion of soil moisture content following rice harvest affects timely sowing and receiving in of poor returns out of these ecosystems. Lack of life saving/supplementary irrigation at critical stages causes further soil moisture scarcity and hampers plant growth and crop productivity per se. Conservation agriculture through zero tillage, crop residue retention and crop rotation involving suitable genotypes influence pulses crop in rotation after rice. Two cropping systems viz., relay cropping of pulses in standing rice, and crop rotation after harvest of rice have potential for popularization and adoption depending on agro-ecosystem involved. Yet, these constrained areas require an understanding of ecology, constraints analysis and situation specific remedies. Keeping these facts, some potential management considerations involving suitable pulses varieties, zero tillage, relay cropping, residue retention, mulching, seed priming, life saving irrigations and foliar sprays of nutrients were suggested that could help in improving pulses productivity under challenging rice fallow conditions.